Space Weather as the Nexus of Applied and Fundamental Space Science: The Need for Separate Funding Mechanisms and Definition - Space Weather Editors (Space Weather)
Abstract This editorial aims at highlighting the importance of keeping space science and space weather fundamental and applied research highly interconnected, but also separate through distinct funding mechanisms. Fundamental and applied space research endeavors are not the same, even though they may share some of the same science regions and approaches, and scientists.